State of the art and abstract bibliography agroforestry research in the Philippines. (Forestry SOA & AB series /PCARRD, 1991)
A compilation of researches and publications on agroforestry in the Philippines, this volume is divided into two parts. The section on state of the art discusses the historical development of agroforestry, government and non-government programs, the roles of agroforestry, agroforestry systems, and Philippine agroforestry research and development. The information, each of which provides a Research Management Information System (RMIS) for computerized searching, and a complete bibliographic descriptions. A researcher and subject index is provided.